Tes Pragmatik Sebagai Penilaian Ranah Psikomotorik Peserta Didik Dalam Belajar Bahasa Arab - Saiful Haq, Muhammad Eep; Raswan (Ukazh: Journal of Arabic Studies, 2025)
In the learning process, it will definitely pass the assessment at the end. Assessment is always closely related to the learning process. One thing that is assessed in the learning process is the psychomotor realm. Psychomotor is an assessment related to students' sensory skills. This research aims to enable readers to gain knowledge about the Pragmatic Test as one of the assessments of the psychomotor realm. The researcher in this research uses a descriptive qualitative method with the type of Library Research or Literature Study. So the source of data from this study is from scientific books and articles related to the research title.